Proposed robust ADRC control of a DFIG used in wind power production - Abdeslam Jabal Laafou; Abdessalam Ait Madi; Youssef Moumani; Adnane Addaim (Institute of Advanced Engineering and Science, 2022)
This work presents the control of the double fed induction generator (DFIG) used in the wind conversion system (WCS). The studied model is based on the control of the two converters grid side converter (GSC) and rotor side converter (RSC), in order to extract the maximum of power and also to keep the direct current (DC) bus voltage constant. The control strategy used here is based on linear active disturbance rejection control (LADRC) controllers. These are known, in the field of control systems, by their performance and robustness and allow a very good rejection of disturbances which can affect the wind system. In addition, this kind of controllers could help to meet the requirements of robustness against the variations of the parameters of the system and the uncertainties of its mathematical model. To validate the effectiveness of the proposed control, the system was modeled and tested by numerical simulation using MATLAB/Simulink software. The results carried out are discussed and analyzed in terms of references tracking, robustness and disturbance rejection. The results obtained have shown shown that the proposed control is promising and useful.